Modification of P&O Method on MPPT with PI Controller to Reduce Power Oscillation during Steady-State Condition - Habibah, Nisrina Rania; Nur Hasanah, Rini; Abidin, Zainul (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2024)
This paper describes an improvement of the Perturb and Observe (P&O) method for maximum power-point tracking (MPPT) on a photovoltaic (PV) cell generating system. The improvement is achieved using a reference voltage () value to respond to perturbation and calculates the power change based on the response. The magnitude of is determined using the reference voltage change . A large will result in a faster tracking but increasing oscillations during steady-state conditions, while a small will reduce oscillations but slowing down the MPPT response. An adaptive value is required to reduce the oscillations which have potential to degrade the efficiency of the PV cell output. A proportional-integral (PI) controller is explored in this paper in determining the most appropriate value. The results showed that oscillations around the MPP point could be reduced by 99%.